First record of some fishes from Libyan waters - Al Hassan, L A J (Indian Journal of Fisheries, 2011)
The Libyan coast of the Mediterranean is about 1,500 km including the bathymetrical areas and closely associated with the major structural features of the African continent. The hydrological conditions of the region are dominated by the presence of three layers of water masses: the surface, the intermediate and the deep layer. Water temperature range from 23Â°C to 24Â°C.